The Effect Of Swimming Training Using Pull Buoys And Fins On Swimming Speed 25 Metres Crawl Style In Athletes SPC Swimming Club - Shayal, Yovan; Sumantri , Ajis; Personi, Megi (Journal of Physical Education and Sports, 2025)
This study aims to the effect of swimming training using pull buoys and fins on swimming speed 25 metres crawl style in SPC Swimming Club athletes. This type of research is quantitative research. The research sample totalled 20 people. The instrument used in this study was the craw style swimming speed test. The results of swimming training tests using pullbuoys and fins on swimming speed 25 metres crawl style in SPC Swimming Club athletes obtained an r table of 0.443 because the correlation coefficient between rxy = 0.96> 0.443 and an influence of 93.00%. Which means that with the discovery of the effect of swimming training using pullbuoys and fins on swimming speed 25 metres crawl style in SPC Swimming Club athletes, training using the pullbuoy and fins method can increase crawl style swimming speed in SPC Swimming Club athletes.